Research of the Fault Diagnosis Method of Automatic Transmission - Zhang Xiaodong; Hu Ning; Bian Xianzhang (Jixie chuandong)
A new method based on logic mathematical fault analysis and support vector machine is provided for fault diagnosis of hydraulic and mechanical fault of automatic transmission（ AT）. The logic mathematical model of AT is established. Then,the logical relationship between fault and fault phenomena is analyzed. The fault simulation analysis is carried out based on AMESim,and the fault sample is provided,a fault identification based on support vector machine is carried out. The reference for developing the intelligent diagnosis system on fault diagnosis of automatic transmission is provided by this method.